Novel VOA using in-plane reflective micromirror and off-axis light attenuation. - Chen, Chihchung (IEEE Communications magazine)
A new off-axis light attenuation configuration combining with a movable reflective micromirror is proposed for variable optical attenuator (VOA) application. Comprehensive study of new comb drive actuators of a two-step structure is done to achieve large displacement of an actuated micromirror for VOA. The measured optical and electrical performances have proven this new design promising for practical applications.